Health Behavior, Level of Hemoglobin A1c, and Quality of Life Among Agricultural Workers of Various Ethnicities in Thai Border Communities - Boonyathee, Sorawit; Ong-Artborirak, Parichat; Seangpraw, Katekaew; Tonchoy, Prakasit; Kantow, Supakan; Bootsikeaw, Sasivimol; Auttama, Nisarat; Choowanthanapakorn, Monchanok; Dokpuang, Dech; Panta, Pitakpong (Frontiers in Medicine, 2022)
Background: Little is known about the glycated hemoglobin (HbA1c) levels and quality of life (QoL) in ethnic minority agricultural workers. We investigated the links among healthcare behaviors, HbA1c levels, and QoL ethnic agricultural workers living in rural areas. Methods: A cross-sectional study was conducted in three northern Provinces of Thailand. Agricultural workers of Indigenous, Hmong, Karen, and Lua communities were recruited. The number of 468 samples were selected using simple random sampling. Data collection was done from interviews using questionnaires, and blood samples were taken. Results: We revealed 56.8% of participants to be female, with an average age of 49.6 years. Also, 56.0% and 34.8% of participants had low and moderate levels of knowledge, respectively. In addition, 56.8% and 30.6% of participants had moderate and low healthcare behaviors, respectively. Also, 51.5% had an abnormal HbA1c level (≥6.5%). We found that 64.7%, 22.9%, and 12.4% had moderate, low, and high QoL, respectively. Multiple linear regression analysis revealed that having a disease current and knowledge score were both significantly related to the healthcare behaviors score (p < 0.05), accounting for 68.4% of the variance. Five variables (ethnicity, BMI, having a disease currently, smoking, and healthcare behaviors) were significantly related to the HbA1c level (p < 0.05), accounting for 23.5% of the variance. Education, health behaviors, and HbA1c level were significantly associated with QoL (p < 0.05). These three factors could explain 79.3% of the variance in QoL among ethnic agricultural workers. Conclusion: Abnormality of the Hba1c level among ethnic minority agricultural workers indicated health problems. Effective health care behaviors modification programs should be developed in accordance with the problems and needs among ethnic minority agricultural workers to enhance their QoL.